MUNICIPAL AVIATION FUNCTIONING AS ONE OF FUTURE TYPES OF THE AVIATION ACTIVITIES - Kharchenko, Volodymyr; Alexeiev, Oleg; Yurchik, Roman; Ali, Ismail (Proceedings of National Aviation University (archive), 2017)
In the article we represent the basic principles of municipal air transport within the metropolis. The main tasks of creating municipal transport are defined to further develop of aviation technologies for municipal economy and life support of the city and its air-transport system. In order to further development of aviation technology in the interests of the urban economy and life of the city, its air transportation system is necessary to decide three main objectives: development of aviation equipment and saturation of City Aviation park by light helicopters which will ensure solving of special tasks for the benefit of urban services, commercial transportation and air operations; development of urban aviation infrastructure, including heliports and helipads; the organization of safe use of the airspace over the city. The use of technology in aviation can be done while ensuring sanitary and environmental standards of environmental protection.